Evaluation of humoral immune response in relation to COVID-19 severity over 1 year post-infection: critical cases higher humoral immune response than mild cases - Bang, Mi-Seon; Kim, Choon-Mee; Cho, Nam-Hyuk; Seo, Jun-Won; Kim, Da Young; Yun, Na Ra; Kim, Dong-Min (Frontiers in Immunology, 2023)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2. We investigated the antibody response against SARS-CoV-2 until 1 year after symptom onset. We collected 314 serum samples from 97 patients with COVID-19. Antibody responses were tested using an indirect immunofluorescence assay (IFA), enzyme-linked immunosorbent assay (ELISA), and plaque reduction neutralization test (PRNT) to detect specific neutralizing antibodies.The positivity rates for neutralizing antibodies at a 1:10 titer cutoff were 58.1% at 1 week, 97.8% at 4 weeks, and 78% at 1 year after symptom onset (53.8% in asymptomatic patients and 89.3% in symptomatic patients). The IFA and anti-S1 ELISA IgG results significantly correlated with neutralizing antibody titers. Critical/fatal cases showed significantly higher antibody titers than the asymptomatic or mild-to-moderate illness groups. Nonetheless, the median number of days to the seroconversion of neutralizing antibodies was 10 and 15 in asymptomatic and symptomatic patients, respectively. The asymptomatic group had a significantly higher neutralizing potency index than the mild-to-severe illness groups.Neutralizing antibodies corresponded to earlier seroconversion but had a shorter presence in the asymptomatic group than in the symptomatic group and were still present 1 year after symptom onset in critical/fatal cases.